CSR Strategy of The Oil and Gas Industry to Enhance the Wellbeing of Coastal Communities Amid Climate Change: A Case Study of PT Pertamina Gas Operation West Java Area in Juntinyuat, Indramayu - Ayodya, Fabian Panji Ayodya; Vany Ardianto; Yedo Kurniawan (Prospect Publishing, 2024)
Climate change exerts multifaceted and profound adverse effects on coastal ecosystems, with Juntinyuat Village, located in Indramayu Regency, serving as a case study of impacted regions. Key consequences include accelerated coastal erosion and the escalation of high wave intensity, both of which pose escalating risks to the livelihoods of populations engaged in tourism, agriculture, and small-scale enterprises. This study aims to analyse the mitigation program implemented through the Corporate Social Responsibility (CSR) approach of PT Pertamina Gas Operation West Java Area (OWJA) with the